Hubungan Volume Sinus Etmoid dengan Tingkat Keparahan Rhinosinusitis Kronik berdasarkan Skor Lund-Mackay pada Suku Toraja-Mandar dan Bugis-Makassar (menggunakan computed tomography scan sinus paranasal) - Syarifuddin, Syahruna; Murtala, Bachtiar; Idris, Nurlaily (UNIVERSITAS SAM RATULANGI, 2021)
Abstract: The volume of the paranasal sinuses varies between individuals and is one of the factors that influence the risk of chronic rhinosinusitis. The severity of chronic rhinosinusitis can be determined based on the Lund-Mackay score on a CT scan. The purpose of this study was to determine the relationship between ethmoid sinus volume and the severity of chronic rhinosinusitis based on the Lund-Mackay score in the Toraja-Mandar and Bugis-Makassar tribes that were subjected to a CT scan of the paranasal sinuses. A total of 103 people aged> 15 years were measured for the ethmoid sinus volume and a Lund-Mackay score was calculated for each side.The subjects consisted of 65 people from Bugis-Makassar ethnicity (63.1%) and Toraja-Mandar ethnicity for 38 people (36.9%). The mean volume of the right ethmoid sinus in the Bugis-Makassar tribe group is 5.44 cm3, in the Toraja-Mandar tribe it is 6.30 cm3 with p-value 0.007, while on the left side is 5.46 cm3 in the Bugis-Makassar tribe and 6.11 cm3 in the Toraja-Mandar tribe with p-value 0.03. There was a significant relationship between ethmoid sinus volume with Lund-Mackay score on each side with a p-value of 0.001 on the right side and a p-value of 0.002 on the left side. conclusion, there is a difference in the mean volume of ethmoid sinuses between the two ethnic groups, where a larger mean volume was found in the Toraja-Mandar ethnic group. The smaller the volume of the ethmoid sinus, the higher the severity of chronic rhinosinusitis.Keywords: ethmoid sinus volume, rhinosinusitis, Toraja tribe Abstrak.Volume sinus paranasal berbeda antar individu dan merupakan salah satu faktor yang mempengaruhi resiko terjadinya rinosinusitis kronik. Derajat keparahan rinosinusitis kronik dapat ditentukan berdasarkan skor Lund-Mackay pada pemeriksaan CT scan.Tujuan penelitian ini adalah untuk mengetahui hubungan volume sinus etmoid dengan derajat keparahan rhinosinusitis kronik berdasarkan skor Lund-Mackay pada sukuToraja-Mandar dan Bugis-Makassar yang dilakukan pemeriksaan CT-scan sinus paranasalis. Sebanyak 103 orang yang berusia> 15 tahun dilakukan pengukuran volume sinus etmoid dan dihitung skor Lund-Mackay pada setiap sisi.Subyek terdiri dari suku Bugis-Makassar 65 orang (63,1%) dan suku Toraja-Mandar 38 orang (36,9. Rerata volume sinus etmoid kanan pada kelompok suku Bugis-Makassar adalah 5,44 cm3, pada sukuToraja-Mandar adalah 6,30 cm3 p-value 0,007, sedangkan pada sisi kiri 5,46 cm3 pada suku Bugis-Makassar dan 6,11 cm3 pada suku Toraja-Mandar p-value 0,03. Terdapat hubungan yang bermakna antara volume sinus etmoid dengan skor Lund-Mackay pada setiap sisi p-value 0,001 pada sisi kanan dan p-value 0,002 pada sisi kiri. Sebagai simpulan, terdapat perbedaan rerata volume sinus etmoid antar kedua kelompok suku, dimana rerata volume lebih besar ditemukan pada kelompok suku Toraja-Mandar. Semakin kecil volume sinus etmoid maka semakin tinggi derajat keparahan rinosinusitis kronik.Kata kunci: volume sinus etmoid, rhinosinusitis, suku Toraja